2003
DOI: 10.1046/j.1432-1033.2003.03930.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular characterization of a laccase from the edible straw mushroom, Volvariella volvacea

Abstract: We have isolated a laccase (lac1) from culture fluid of Volvariella volvacea, grown in a defined medium containing 150 µm CuSO4, by ion‐exchange and gel filtration chromatography. Lac1 has a molecular mass of 58 kDa as determined by SDS/PAGE and an isoelectric point of 3.7. Degenerate primers based on the N‐terminal sequence of purified lac1 and a conserved copper‐binding domain were used to generate cDNA fragments encoding a portion of the lac1 protein and RACE was used to obtain full‐length cDNA clones. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 61 publications
4
33
0
1
Order By: Relevance
“…Generally, Lccs occur as a series of isozymes encoded by a family of genes. Many Lcc isozymes have been purifi ed, and their encoding genes have been cloned from various white-rot basidiomycetes (Chen et al 2004;Hoegger et al 2004;Baldrian 2006). Lentinula edodes (Berk.)…”
Section: Masaru Nagai · Yuichi Sakamoto · Keiko Nakade Toshitsugu Satomentioning
confidence: 99%
“…Generally, Lccs occur as a series of isozymes encoded by a family of genes. Many Lcc isozymes have been purifi ed, and their encoding genes have been cloned from various white-rot basidiomycetes (Chen et al 2004;Hoegger et al 2004;Baldrian 2006). Lentinula edodes (Berk.)…”
Section: Masaru Nagai · Yuichi Sakamoto · Keiko Nakade Toshitsugu Satomentioning
confidence: 99%
“…Another white laccase, extracted from Phellinus ribis, binds two zinc ions, one manganese ion and one copper ion, and can oxidize various substrates [61]. Another strain of white laccase is found in Volvariella volvacea [62]. The presence of white laccase poses many questions.…”
Section: White Laccasementioning
confidence: 99%
“…A range of enzymes are synthesized during mushroom growth on these substrates including laccases [benzenediol:oxygen oxidoreductases (EC 1.10.3.2)], copper-containing enzymes that catalyze the oxidation of a broad spectrum of phenolic compounds and non-phenolic substrates using molecular oxygen as the electron acceptor. Laccases are widely distributed among fungi, where they have been assigned roles in lignin degradation (Bourbonnais et al 1995;Eggert et al 1997), in rendering phenolic compounds less toxic via oxidative coupling and polymerisation (Bollag et al 1988; Moldes and Sanroman 2006) and in mushroom fruit-body morphogenesis (Zhao and Kwan 1999;Chen et al 2004). Laccases may be either constitutive or inducible, and many factors including culture parameters (Fu et al 1997), heavy metals (Baldrian and Gabriel 2002;Chen et al 2003) and aromatic compounds (Scheel et al 2000) are reported to influence enzyme production in different fungal species.…”
Section: Introductionmentioning
confidence: 99%